Increased neuronal activation in sympathoregulatory regions of the brain and spinal cord in type 2 diabetic rats. (2nd August 2021) - Sethi, Shivani; Augustine, Rachael A.; Bouwer, Gregory T.; Perkinson, Michael R.; Cheong, Isaiah; Bussey, Carol T.; Schwenke, Daryl O.; Brown, Colin H.; Lamberts, Regis R.
Abstract: Increased cardiac sympathetic nerve activity in type 2 diabetes mellitus (DM) suggests impaired autonomic control of the heart. However, the central regions that contribute to the autonomic cardiac pathologies in type 2 DM are unknown. Therefore, we tested the hypothesis that neuronal activation would be increased in central sympathoregulatory areas in a pre‐clinical type 2 DM animal model. Immunohistochemistry in 20‐week‐old male Zucker diabetic fatty (ZDF) rats revealed an increased number of neurones expressing ΔFosB (a marker of chronic neuronal activation) in the intermediolateral column (IML) of the spinal cord in DM compared to non‐diabetic (non‐DM) rats ( P  < 0.05). Rostral ventrolateral medulla (RVLM) neurones activate IML neurones and receive inputs from the hypothalamic paraventricular nucleus (PVN), as well as the nucleus tractus solitarius (NTS) and area postrema (AP), in the brainstem. We observed more ΔFosB‐positive noradrenergic RVLM neurones ( P  < 0.001) and corticotrophin‐releasing hormone PVN neurones ( P  < 0.05) in DM compared to non‐DM rats. More ΔFosB‐positive neurones were also observed in the NTS ( P  < 0.05) and AP ( P  < 0.01) of DM rats compared to non‐DM rats. Finally, because DM ZDF rats are obese, we also expected increased activation of pro‐opiomelanocortin (POMC) arcuate nucleus (ARC) neurones in DM rats; however, fewer ΔFosB‐positive POMC ARC neurones were observed in DM compared to non‐DM rats ( P  < 0.01). In conclusion, increased neuronal activation in the IML of type 2 DM ZDF rats might be driven by RVLM neurones that are possibly activated by PVN, NTS and AP inputs. Elucidating the contribution of central sympathoexcitatory drive in type 2 DM might improve the effectiveness of pharmacotherapies for diabetic heart disease. Abstract : The brain regions that contribute to the autonomic cardiac pathologies in type 2 diabetes mellitus are unknown. We identified in a diabetic animal model, increased neuronal activation in the intermediolateral column, rostral ventrolateral medulla and specifically the corticotrophin‐releasing hormone neurones in the paraventricular nucleus region. Because current therapies for cardiac pathologies in diabetes have predominantly less effective peripheral targets, our findings are the first step to suggest that alternative treatment strategies against autonomic dysfunction in diabetes might be available in specific central regions.